Superbloom : how technologies of connection tear us apart - Carr, Nicholas G., 1959- (W.W. Norton & Company, 2025)
"A bracing exploration of how social media has warped our sense of self and society. From the telegraph and telephone in the 1800s to the internet and social media in our own day, the public has welcomed new communication systems. Whenever people gain more power to share information, the assumption goes, society prospers. Superbloom tells a startlingly different story. As communication becomes more mechanized and efficient, it breeds confusion more than understanding, strife more than harmony. Media technologies all too often bring out the worst in us. A celebrated commentator on the human consequences of technology, Nicholas Carr reorients the conversation around modern communication, challenging some of our most cherished beliefs about self-expression, free speech, and media democratization. He reveals how messaging apps strip nuance from conversation, how 'digital crowding' erodes empathy and triggers aggression, how online political debates narrow our minds and distort our perceptions, and how advances in AI are further blurring the already hazy line between fantasy and reality. Even as Carr shows how tech companies and their tools of connection have failed us, he forces us to confront inconvenient truths about our own nature. The human psyche, it turns out, is profoundly ill-suited to the 'superbloom' of information that technology has unleashed. With rich psychological insights and vivid examples drawn from history and science, Superbloom provides both a panoramic view of how media shapes society and an intimate examination of the fate of the self in a time of radical dislocation. It may be too late to change the system, Carr counsels, but it's not too late to change ourselves"--